IMPLEMENTASI NILAI-NILAI BUDAYA LOKAL MARIMOI NGONE FUTURU (BERSATU KITA TEGUH) DALAM MEWUJUDKAN CINTA TANAH AIR MELALUI PEMBELAJARAN KURIKULUM MERDEKA DI SMA KOTA TERNATE - Rustam Hasim; Mohtar Kamisi (Universitas Khairun, 2023)
This research discusses the implementation of local cultural values, Marimoi Ngone Future (United We Are Firm) in realizing love for the homeland through civic education learning at Ternate City High School. The background to this research explains that Ternate Island consists of various ethnic groups, has cultural diversity and unique, exotic traditions that enrich the values of Indonesian life. Ternate Island is one of the areas in North Maluku Province which is also rich in art and culture. Ternate is still very attached to the sultanate, this is because the term Ternate refers to the four centers of the sultanate in North Maluku, namely the Ternate Sultanate, Tidore Sultanate, Jailolo Sultanate and Bacan Sultanate which is known as Moloku Kie Raha which means the four mountains of Maluku with the motto Marimoi Ngone Futuru which means United We Stand.Marimoi Ngone Futuru is found in the symbol of North Maluku in the form of a pentagonal shield, which contains various objects, as well as the inscription 1999, which is the year the North Maluku province was founded. The meaning of the image is (1). The star symbolizes the Almighty Godhead. (2). Mountains are a symbol of abundant forest product wealth. The sea is a symbol of unity and oneness. (3), Rice, cloves, nutmeg and palm leaves are symbols of prosperity. (4). Salawaku and Parang as symbols of heroism. (5). The motto